MANAJEMEN LABA, CORPORATE GOVERNANCE, KUALITAS AUDITOR EKSTERNAL DAN AGRESIVITAS PAJAK - Cahya Adhi Kusuma; Amrie Firmansyah (Universitas Mercu Buana, 2018)
ABSTRACT This study is aimed to examine the effect of earnings management, corporate governance, and auditor quality on agresivitas pajak. Using samples from manufacturing companies listed on the Indonesia Stock Exchange in the period 2011 to 2015, the data will be examined with regression multiple analysis. The results of this study indicate that earnings management has a positive impact to tax aggresiveness. While corporate governance which consists of the percentage of institutional ownership, the percentage of independent commissioners, and the total member of the audit committee shows that those have no impact to agresivitas pajak. Lastly, auditor quality also have no impact to agresivitas pajak as well. KEYWORDS: Earnings Management, Corporate Governance, Auditor Quality, Tax Aggresiveness